ANALISIS POTENSI LIKUIFAKSI DENGAN PENDEKATAN PROBABILISTIK (PERFORMANCE-BASED EVALUATION) DI KOTA PADANG, SUMATERA BARAT - Rena Misliniyati; FX Toha; I Wayan Sengara (Universitas Bengkulu, 2019)
Evaluation of liquefaction potential by the conventional way are based on deterministic methods. The methods use only one condition of earthquake load as parameter in liquefaction analysis. Actually, the strength of earthquake loads are varies. In the other words, there is the uncertainty magnitude of earthquake loading. The uncertainty can be taken into analysis only by using a probabilistic approach. This study describes how to analyze liquefaction by probabilistic method. The method used was performance-based evaluation, developed byKramer and Mayfield (2005, 2007). This method include contributions from all levels of magnitude earthquake (hazard levels) in liquefaction analysis. The research location is in Padang, West Sumatra. Soil Investigation data used are N-SPT and shear wave velocity spread in the city of Padang. Earthquake load parameters used were obtained from PSHA and deagregation analysis. The results of this study show the variation of liquefaction potential across the city of Padang based on liquefaction return period. The location with great potentialfor liquefaction (FS <1) by the probability more than 50% were in the coastal region and northern parts of Padang.